1983
DOI: 10.4102/abc.v14i2.1160
|View full text |Cite
|
Sign up to set email alerts
|

The taxonomic position of C3 and C4 <i>Alloteropsis semialata</i> (Poaceae) in southern Africa

Abstract: Alloteropsis semialata (R. Br.) Hitchc. sensu Chippindall (1955) and Clayton (in press) is the only known grass species in which elements with both non-Kranz and Kranz leaf blade anatomy, and therefore with C3 and C4 photosynthetic pathways are included. In the past, two taxa had been recognized, but the characters used to separate them were found to be unreliable, so they were united. However, study of voucher specimens for anatomical and physiological work has shown that C3 and C4 taxa may be separated on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…A similar difference in leaf morphology exists between the C 3 and C 4 subspecies of A. semialata (Gibbs-Russell, 1983), highlighting potential links between photosynthetic pathway evolution and changes to leaf anatomy and morphology.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A similar difference in leaf morphology exists between the C 3 and C 4 subspecies of A. semialata (Gibbs-Russell, 1983), highlighting potential links between photosynthetic pathway evolution and changes to leaf anatomy and morphology.…”
Section: Discussionmentioning
confidence: 75%
“…Gibbs-Russell (1983) designated the C 3 and C 4 variants of A. semialata as subspecies rather than separate species because herbarium specimens included apparent intermediates between the C 3 and C 4 forms and therefore suggested there was gene flow between them. However, recent molecular phylogenies have shown some grass genera to be polyphyletic (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The two taxa were distinguished by comparing the leaf blades according to the guidelines of Gibbs Russell (1983), summarized as follows: Subspecies semialata has linear leaf blades, 3-5 (6) mm wide, usually curved upwards, tapering gradually to the tip and sparsely hairy. C4 anatomy manifests in veins on basal parts of the sheaths, forming broad flat ribs 0.5-l.lmm across and is visible with a hand lens.…”
Section: Morphologymentioning
confidence: 99%
“…Alloteropsis semialata is a unique grass, including both Kranz and non‐Kranz leaf anatomies, and therefore C 3 and C 4 photosynthetic modes, within this one species (Ellis 1974a,b). Gibbs Russell (1983) re‐examined the taxonomic position of A. semialata by using vegetative characters and classified the Kranz and the non‐Kranz forms into the subspecies semialata and eckloniana , respectively. Previous studies on the photosynthetic characteristics of the two subspecies have demonstrated that the respective C 4 and C 3 characteristics correspond to the activities of photosynthetic enzymes, carbon isotope ratios and CO 2 gas exchange (Brown 1977; Barrett, Frean & Cresswell 1983; Frean, Ariovich & Cresswell 1983a; Frean et al .…”
Section: Introductionmentioning
confidence: 99%
“…Liebenberg & Fossey (2001) reported that in South Africa the distributions of the two subspecies overlap and they are growing in mixed populations. Although some authors doubt that the two photosynthetic forms constitute the same species (Liebenberg & Fossey 2001), it seems certain that they are taxonomically close (Gibbs Russell 1983).…”
Section: Introductionmentioning
confidence: 99%